Cortical N‐acetylaspartate concentrations are impacted in chronic stroke but do not relate to motor impairment: A magnetic resonance spectroscopy study. Issue 10 (3rd May 2021) - Ferris, Jennifer K.; Neva, Jason L.; Vavasour, Irene M.; Attard, Kaitlin J.; Greeley, Brian; Hayward, Kathryn S.; Wadden, Katie P.; MacKay, Alex L.; Boyd, Lara A.
Abstract: Magnetic resonance spectroscopy (MRS) measures cerebral metabolite concentrations, which can inform our understanding of the neurobiological processes associated with stroke recovery. Here, we investigated whether metabolite concentrations in primary motor and somatosensory cortices (sensorimotor cortex) are impacted by stroke and relate to upper‐extremity motor impairment in 45 individuals with chronic stroke. Cerebral metabolite estimates were adjusted for cerebrospinal fluid and brain tissue composition in the MRS voxel. Upper‐extremity motor impairment was indexed with the Fugl‐Meyer (FM) scale. N ‐acetylaspartate (NAA) concentration was reduced bilaterally in stroke participants with right hemisphere lesions ( n = 23), relative to right‐handed healthy older adults ( n = 15; p = .006). Within the entire stroke sample ( n = 45) NAA and glutamate/glutamine (GLX) were lower in the ipsilesional sensorimotor cortex, relative to the contralesional cortex (NAA: p < .001; GLX: p = .003). Lower ipsilesional NAA was related to greater extent of corticospinal tract (CST) injury, quantified by a weighted CST lesion load ( p = .006). Cortical NAA and GLX concentrations did not relate to the severity of chronic upper‐extremity impairment ( p > .05), including after a sensitivity analysis imputing missing metabolite data for individuals with large cortical lesions ( n = 5). Our results suggest that NAA, a marker of neuronal integrity, is sensitive to stroke‐related cortical damage and may provide mechanistic insights into cellular processes of cortical adaptation to stroke. However, cortical MRS metabolites may have limited clinical utility as prospective biomarkers of upper‐extremity outcomes in chronic stroke.